2014
DOI: 10.1021/jp411385u
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Specific Long-Range Correlations on Interfacial Water Driven by Hydrogen Bond Fluctuations

Abstract: SI TextIn our experiments we measure (in situ, via online electrospray mass spectrometry, ES-MS, Kyoto University) relative anion populations, χ = P 127 /P 79+81 = [I -]/[Br -], in the water 'films' produced upon blowing up drops of sodium salt solutions by a high-speed gas as a function of ion additions in the 0.1 -10 µM range. Here we summarize the key mechanisms that give rise to mass spectral signals. Liquid solutions (injected as jets into the spraying chamber of the mass spectrometer) are sheared into pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 100 publications
0
12
0
Order By: Relevance
“…The related question of the propensity of ions in a liquid–vapor planar interface has been studied over several decades. It is emphasized that the forces that determine the location of multiple ions in a planar interface are not the same as those in charged droplets regardless of their size. The reason is that the conductivity of the aqueous droplets drives the excess ions nearer to the surface and the counterions toward the interior .…”
Section: Introductionmentioning
confidence: 99%
“…The related question of the propensity of ions in a liquid–vapor planar interface has been studied over several decades. It is emphasized that the forces that determine the location of multiple ions in a planar interface are not the same as those in charged droplets regardless of their size. The reason is that the conductivity of the aqueous droplets drives the excess ions nearer to the surface and the counterions toward the interior .…”
Section: Introductionmentioning
confidence: 99%
“…Some ions accumulate at a specific depth layer of water–hydrophobes (e.g., air, oil, and biomembranes) interfaces, while other ions prefer to remain in bulk water and react homogeneously. Long-chain carboxylate ions, due to the amphiphilic property, play key roles in the nucleation, growth, and photochemical aging process of atmospheric aerosol. For example, bubble-bursting from surface of the ocean is responsible for enriching marine aerosols with long-chain carboxylate ions, ,,, thereby influencing the chemistry of marine boundary layers. , Long-chain carboxylate ions act as a film covering atmospheric particles, directly confirmed by field measurement studies. Recent studies have suggested long-chain carboxylate ions could induce cloud droplet formation, thereby affecting global climate change. , Benzoate ion, C 6 H 5 -COO – , has been recently found to be one of the most abundant organic species observed in PM 2.5 of polluted areas, where the concentration on PM 2.5 exceeds 1 μg/m 3 …”
Section: Introductionmentioning
confidence: 99%
“…7-10 These concentration (or structural) fluctuations are brief (tens of picoseconds) inhomogeneities in the ∼1 nm scale that happen to peak in the concentration ranges that give rise to thermodynamic and transport properties anomalies in binary mixtures. [11][12][13][14][15][16][17] milliseconds to years) non-covalent aggregates detected by dynamic light scattering experiments in many systems. [18][19][20][21][22] These aggregates also appear in the mass spectra of liquid jets produced by adiabatic expansion of solutions of hydrophobic species in aqueous organic mixtures.…”
Section: Introductionmentioning
confidence: 99%